Grants and foundations the contributions of Frederick C. and Robert M. Grant to the Chicago Society of Biblical Research - Pardee, Nancy D. (2020)
This article highlights the scholarship and service of Frederick C. Grant and Robert M. Grant, father and son respectively, both of whom helped to build and maintain a strong and enduring foundation for the Chicago Society of Biblical Research in the twentieth century. Their extraordinary intellects and their enormous academic productivity combined with their insistence on understanding the biblical texts in their historical context to make their voices forces to be reckoned with during their years in the society and helped to make the society a vibrant, engaging, and intellectually rigorous forum for biblical research. Equally important, however, was their service to the society, work that helped to ensure that this forum was structurally sound and would continue to flourish well into the future.
Keywords: Frederick M. Grant; Robert C. Grant; Grant, Frederick Clifton (1891-1974); Grant, Robert McQueen (1917-2014); Chicago Society of Biblical Research; Biblical Research; New Testament scholarship